PEMBELAJARAN IPAS SEKOLAH DASAR DALAM KURIKULUM MERDEKA DENGAN PENDEKATAN GAMIFIKASI KEARIFAN LOCAL - Wiwik Wiwik (CV. ADIBA AISHA AMIRA, 2024)
The aim of this research is to find out how to implement science and science learning in the independent curriculum using a traditional game approach with local wisdom. 6 indicators of the Pancasila student profile, namely having noble character, independence, critical reasoning, creativity, working together and global diversity. One of the innovative science lessons that can strengthen the profile of Pancasila students is with traditional games. The method in this research is to use a literature review sourced from journals, proceedings, books and articles related to the research focus. The results of research on traditional games that are linked to science and science learning can shape children's positive character. These values are educational values, sportsmanship values, mutual cooperation values, democratic values, moral values and courage values. Implementing traditional games can internalize positive values in children's souls. So by cultivating these characters we can implement the Pancasila student profile contained in the independent curriculum. One of the tug of war games is that children are expected to be able to understand the concepts of science material related to movement and force and apart from that, children have the habit of working together in teams. Pancasila students must be willing to carry out activities together, help each other, so that work is easy and light, and by working together to encourage collaboration and care. The social-emotional aspect is found in suppressing emotions when annoyed with friends, and being patient in waiting your turn.